Implementasi Pembiasaan Aturan Bermain dalam Kegiatan Sehari-Hari sebagai Upaya Membentuk Karakter Disiplin Anak Usia 4-5 Tahun - Puspita Asih, Rah Ajeng; Elan; Maulana Rizqi, Anggi (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2025)
PThis study aims to explore the implementation of habituation of the rules of the game in daily activities and its contribution to the formation of disciplinary character in children aged 4-5 years at RA Raihan Persis 27 Tasikmalaya City. The research method employed is a descriptive qualitative approach, utilizing data collection techniques that include observation, interviews, and documentation. The results showed that the habituation of the rules of the game that is consistently applied through structured play activities can foster a disciplined attitude in children. Children not only learn to obey the rules, wait their turn, and use objects according to their function, but also begin to show social care by reminding each other. Teachers play an important role as role models, facilitators, and evaluators, and use various strategies, including role models, visual media, and morally charged stories. Evaluation is conducted regularly to monitor children's development in discipline and adjust learning strategies. This study concludes that habituation of the rules of the game, which is carried out consistently and supported by the role of the teacher and communication with parents, is effective in shaping the disciplinary character of early childhood. This study also recommends the development of innovative models of habituation of rules of the game and further research in other early childhood education institutions to strengthen the findings and expand the application of discipline character-building strategies.